Inovasi Program Sakera Mesem dalam Meningkatkan Kualitas Pelayanan Publik - Nadiatussilmi, Nadiatussilmi; Hayat, Hayat; Anadza, Hirshi (Jurnal Indonesia Sosial Sains, 2022)
This research is a significant research in selecting the idea of ​​implementing policies related to the improvement of a Sakera Mesem program and the constraint factors that led to the idea of ​​regulating the quality of population document services at the Population and Civil Registration Office of Sampang Regency. The purpose of this research is to describe and analyze the innovations of the Sakera Mesem program in improving the quality of public services at the Department of Population and Civil Registration of Sampang Regency. In this study used qualitative research methods, qualitative research methods are research that analyzes something that appears in the field, data collection techniques used are interviews and observations and documentation. From the results of the discussion, it can be obtained the results of research that analyzes the development of the "Sakera Mesem" program of the Dispenduk Capil of Sampang Regency which has been applied and realized properly and correctly in its implementation to improve services for the community. Based on this, there are 6 theories of service standards seen from the side of community services to support the realization of the "Saekera Mesem" program, namely service procedures, completion time, service fees, service products, places and supporting tools and professionalism of service personnel, but there is an analysis The obstacle is internet services that are not adequate as a whole and there is an analysis of assistants, namely facilities taken from village income sources, namely PCs, scanners and printers, recording devices, internet and operators, and there are allocation funds from the government in implementing this program. So, it can be said that Sakera Mesem's innovation is of high quality, seen from the standard of service provided to the community, which is maximal and meets the specified service quality criteria.